Sistem Pendukung Keputusan Dengan Metode Topsis Untuk Menentukan Kelayakan Dokumen Penggunaan Tenaga Kerja Asing Di PT Singawa Partner Indonesia - Intan Hati Bu’ulolo; Habibah Nurfauziah; Faiz Rafdhi; Nur Kumala Dewi; Warno (LPPMPP Yayasan Sejahtera Bersama Bengkulu, 2025)
This study aims to develop a decision support system using the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method to determine the eligibility of foreign worker documents at PT Singawa Partner Indonesia. The system is designed based on five main criteria, namely document completeness, legality, international work experience, language proficiency, and job suitability. To evaluate user acceptance of the system, the Technology Acceptance Model (TAM) approach was used, involving three variables: Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Attitude Toward Using (ATU), with a total of 30 internal respondents. The evaluation results showed that the system achieved a high level of acceptance with an average total score of 84.3%, indicating that the system is useful, easy to use, and favored by users. Therefore, the system is deemed effective and suitable for implementation in the selection process for foreign worker documents within the company environment. Keywords— Sistem Pendukung Keputusan, TOPSIS, Tenaga Kerja Asing, Kelayakan Dokumen, TAM